2017
DOI: 10.1136/bmjopen-2016-014573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of demands, usage and unmet needs for emergency care in Yaoundé, Cameroon: a cross-sectional study

Abstract: ObjectivesTo assess the burden of emergent illnesses and emergency care system usage by Yaoundé residents and to evaluate unmet needs for emergency care and associated barriers.DesignA cross-sectional study using a community-based survey.SettingYaoundé, Cameroon.ParticipantsAll residents living in Yaoundé were selected as the target population to investigate the needs and usage of emergency care in Yaoundé. 14 households in every health area (47 in total) were selected using 2-stage sampling.Primary outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 16 publications
4
36
2
1
Order By: Relevance
“…This might indicate that poor individuals predominately suffered from unmet need due to the health system responsibility. In line with our finding, other studies [34] [9,11,14,31] also showed that lower economic status was associated with a higher degree of overall unmet need as well as system-related unmet need. Poor people not only had lower affordability but also might live in areas with worse access to healthcare services, which might in turn make them vulnerable to unmet need.…”
Section: Discussionsupporting
confidence: 92%
“…This might indicate that poor individuals predominately suffered from unmet need due to the health system responsibility. In line with our finding, other studies [34] [9,11,14,31] also showed that lower economic status was associated with a higher degree of overall unmet need as well as system-related unmet need. Poor people not only had lower affordability but also might live in areas with worse access to healthcare services, which might in turn make them vulnerable to unmet need.…”
Section: Discussionsupporting
confidence: 92%
“…[7] Affordability and a range of socio-economic factors are also key barriers to the ECS as a whole. [31] Registries Standardized emergency care registries are largely absent in most LMICs, due to a lack of standard clinical management and documentation in prehospital and facility settings. [7,32] However, the establishment of registries is slowly increasing in response to the growing body of evidence in support of trauma registries.…”
Section: Barriers To Carementioning
confidence: 99%
“…Most EMS systems were predominantly basic life support, government operated, and involved a fee (12,13) . Furthermore, a recent study in Yaoundé Cameroon showed a very high unmet need of EMS, in this survey 68.8% of respondents reported unmet needs for emergency care (14) . Before the establishment of emergency medicine in the Africa, emergencies that needed a specific specialist not in attendance were given to whatever physician could be found, regardless of expertise.…”
Section: Introductionmentioning
confidence: 98%
“…Prehospital emergency care in Cameroon is basically absent, however in the major towns of Yaoundé and Douala, this service is provided by the French Service d'Aide Médicale Urgente (SAMU) system. The SAMU is a prepaid system; however, usage of SAMU is very limited due to high cost, poor equipment and lack of trained healthcare professionals (14) . The last two years have witnessed some achievements in the field of emergency medicine in Cameroon which include: International organizations and foreign countries have also contributed by providing aid to Cameroon's health system in general, and to EDs in particular.…”
Section: Ems In Cameroonmentioning
confidence: 99%